Eliminating the need for fasting with oral administration of bisphosphonates - Pazianas M; Abrahamsen B; Ferrari S; Russell RGG (Dove Medical Press, 2013)
Michael Pazianas,1 Bo Abrahamsen,2,3 Serge Ferrari,4 R Graham G Russell1,5 1The Botnar Research Center and Oxford University Institute of Musculoskeletal Sciences, Oxford, UK; 2Department of Medicine F, Gentofte Hospital, Hellerup, 3Odense Patient data Explorative Network (OPEN) Institute of Clinical Research, University of Southern Denmark, Odense, Denmark; 4Division of Bone Diseases, Faculty of Medicine, Geneva University Hospital, Geneva, Switzerland; 5Mellanby Centre for Bone Research, University of Sheffield, Sheffield, UK Abstract: Bisphosphonates are the major treatment of choice for osteoporosis, given that they are attached preferentially by bone and significantly reduce the risk of fractures. Oral bisphosphonates are poorly absorbed (usually less than 1% for nitrogen-containing bisphosphonates) and when taken with food or beverages create complexes that cannot be absorbed. For this reason, they must be taken on an empty stomach, and a period of up to 2 hours must elapse before the consumption of any food or drink other than plain water. This routine is not only inconvenient but can lead to discontinuation of treatment, and when mistakenly taken with food, may result in misdiagnosis of resistance to or failure of treatment. The development of an enteric-coated delayed-release formulation of risedronate with the addition of the calcium chelator, ethylenediaminetetraacetic acid (EDTA), a widely used food stabilizer, eliminates the need for fasting without affecting the bioavailability of risedronate or its efficacy. Keywords: bisphosphonates, osteoporosis treatment, absorption, EDTA, osteoclasts